Pendidikan Multikultural Berbasis Digital sebagai Strategi Penguatan Pendidikan Inklusif di Sekolah Dasar - Nailatun Nisa; Elisa Dwi Nur Aini; Haifa 'Inayatun 'Azizah; Yuana Amelia; Dian Armania; An-Nisa Apriani; Yusinta Dwi Ariyani (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
Cultural, ethnic, religious, and social diversity among elementary school students is a reality that requires effective management through learning practices that promote respect for differences. Multicultural education plays a crucial role in fostering tolerance and mutual respect, while inclusive education ensures equal learning opportunities for all students without discrimination. At the same time, digital transformation has created new opportunities to integrate these approaches by utilizing technology as an adaptive, interactive, and accessible learning medium. This study aims to critically examine the role of digital-based multicultural education as a strategy for strengthening inclusive education in elementary schools. The research employed a library research method with a qualitative descriptive approach. Data were collected from relevant academic sources, including books, scholarly journals, and scientific documents, and analyzed using content analysis through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that integrating multicultural education with digital technology enhances students’ understanding of diversity, promotes tolerance, and expands learning accessibility for all learners, including those with special educational needs. The successful implementation of this approach depends on teachers’ digital competencies, the availability of supporting technological infrastructure, and school policies that promote an inclusive culture. Therefore, digital-based multicultural education can serve as an effective strategy for creating equitable, inclusive, and diversity-responsive learning environments in elementary schools. The findings are expected to provide a conceptual reference for policymakers and educators in developing technology-supported inclusive learning practices.